Adenocarcinoma in continent anal urinary diversion: is a sigma rectum pouch a surgical option after failed ureterosigmoidostomy? - Honeck, Patrick; Kienle, Peter; Younsi, Nina; Thüroff, Joachim W.; Stein, Raimund (Urology, 2017)
Objective: To report our experience of radical resection of secondary cancers after ureterosigmoidostomy. Ureterosigmoidostomy was the most common continent urinary diversion before the era of continent cutaneous diversion and neobladders, specifically in children. When performed for bladder exstrophy, patients will live with this kind of diversion for quite a long time. As a result, urologists will be confronted with patients presenting with an adenocarcinoma in their ureterosigmoidostomy. In most cases reported in the literature, an ileal conduit was used for urinary conversion. However, nowadays an ileal loop must not be the only solution for patients with a long life expectancy. Materials and Methods: Between 2004 and 2015, 6 patients were treated for an adenocarcinoma in their ureterosigmoidostomy. All patients underwent radical resection of the tumor-bearing sigmoid colon. After thorough preoperative informed consent concerning the choice of future urinary diversion, such as conversion to an ileal conduit, construction of a continent catheterizable pouch, or repeat continent anal diversion, 4 patients chose a repeat continent anal urinary diversion. Results: Up to this date, no complications or recurrences were seen after a median follow-up of 35 months. Conclusion: In patients with secondary malignancy of the colon, radical resection of the tumor-bearing bowel segment is mandatory. A repeat continent anal urinary diversion appears to be a feasible alternative to secondary urinary diversion after resection of the tumor-bearing sigmoid colon. However, a longer follow-up is required to determine whether the risk of secondary malignancy remains unchanged, and whether the risk is increased or decreased.